EFFECTIVENESS OF PALATE CLEANSERS FOR EVALUATING SOURNESS - VICKERS, ZATA; MORRIS, ERIN E.; SAVARIA, MÉLANIE (Journal of sensory studies, 2008)
ABSTRACT The objective of this study was to compare four palate cleansing strategies (crackers, carrots, water and nothing) for their effectiveness in evaluating the sourness of a fruit‐flavored beverage. Forty panelists rated the sourness intensity of five orange drink samples that varied in citric acid content. Each subject participated in four sessions, one for each palate cleanser. As expected, sourness increased with increasing citric acid content. There were no significant differences between any of the palate cleansers for the discrimination among the sourness levels. Sourness neither increased (buildup) nor decreased (adaptation) during the session with any of the palate cleansing strategies. Using carrots or water provided similar discrimination to crackers, but the panelists rated the sourness higher after using carrots or water as a palate cleanser than after using the cracker. PRACTICAL APPLICATIONS Palate cleansers are widely used during sensory evaluation of foods. We suspect that part of the reason people use them is because they lower the intensity of residual flavors, leading people to believe the flavors have been removed from their mouth. Our results show that residual cleansers can produce changes in the flavor of subsequently tasted products. Because the nature and extent of these changes will logically depend on the specific product and the specific palate cleansing strategy, experiments need to be conducted to provide these measures.